3D Printable Recycled Textiles: Material Innovation and a Resurrection of the Forgotten "shoddy" Industry. (3rd July 2017) - Vettese Forster, Samantha
Abstract: This paper will disseminate an interdisciplinary project, undertaken at Edinburgh Napier University between the Design and Advanced Materials. Several 3D printable materials are commercially available that use recycled material, including post consumer PET bottles and wood, but none that incorporate textiles. This project was funded by the Textiles Future Forum in collaboration with four Scottish textile companies who provided "waste" textiles (wool, cashmere and leather), to be used in this way. In the cases of the wool and cashmere, this is predominantly selvedge waste from the looms and knitting machines, unusable scraps and fluff swept up from under the machinery. The leather was recycled from airplane seats, returned to the manufacturers for disposal. The paper will outline the relationship between 3D printing and the textile and fashion industries at this time and the beneficial traits of 3D printing technology, the historical context of the project, particularly the advent of "shoddy", a now seldom used material with many extremely similar traits to this projects inception, how these historical processes have common characteristics with the procedures used in this project, a brief outline of how the 3D printable materials were created and an evaluation of the embodiment of the narrative of Scottish tradition and "authenticity" in the materials.